ECOLOGICAL ASSESSMENT OF THE NITRATES CONTENT VARIABILITY IN VEGETABLE AND FRUIT CROPS IN THE DNIPROPETROVSK REGION - Харитонов, М. М.; Лазарєва, О. М.; Лемішко, С. М. (Scientific Progress & Innovations, 2015)
The aim of this work is the ecological assessment of quantitative determination of nitrate in vegetable and fruit production after conducting field experiments in Dnipropetrovsk region. The results of the determination of nitrates in vegetables, fruits and berries, which are most often used in the human diet are presented. Control of nitrate content was carried out by potentiometric method using an ion-selective electrode. The results of the research showed the greatest exceedance in such vegetables: radishes, beets, carrots and pumpkin – in 6 samples 5 exceed MPC. In the determination of nitrate content in potato 12 samples from 46 exceed the MCL, in cabbage – 2 samples of 12, and pepper – in 2 samples from 9 exceed the MPC. The fruits and berries studied in our work on the nitrate concentration belong to the group of low concentration (up to 100 mg/kg). The lowest nitrate content was found in green peas.